Analisis Persepsi Peserta Didik mengenai Efektivitas Video Pembelajaran dan Quizizz pada Hasil Belajar IPAS Peserta Didik Kelas V SDN Purwoyoso 03 Kota Semarang - Cholisah, Nur Hikmah Al; Kurnianto, Bagas (Jurnal Simki Pedagogia, 2025)
The utilization of learning media such as learning videos and quizizz applications is one of the innovations in improving the quality of learning in the classroom. Learners tend to form perceptions of these media based on the quality of the display, delivery of material, and interactive and fun learning experiences. Learners' perceptions of learning video and quizizz media are how they recognize, understand, and interpret their experiences when using these two media in the learning process. This study aims to analyze how students' perceptions of the use of learning video media and quizizz media and what factors influence students' perceptions of the effectiveness of learning videos and quizizz. The method used in this research is descriptive with qualitative analysis and the research site is carried out at Purwoyoso 03 State Elementary School in Semarang City with informants of the principal, grade V teacher, and 5 students from each class. The data collection process is carried out by observation, interview, questionnaire, and documentation. The results showed that fifth grade students have positive perceptions of learning videos that increase understanding, focus, and interest in learning, as well as quizzes that encourage engagement, motivation, and understanding through interactive features. This perception is influenced by physical conditions, expectations, understanding of the material, involvement, and habits in using the media.